(untitled) (Global Journal of Science Frontier Research, 2023)
Without doubt weather patterns are drastically changing And for the worse Those aged 70 and above as opposed to younger generations can attest to this climate anomaly In recent times hotter temperatures and heat waves floods droughts desertification erratic rains rising water levels in lakes and seas Indian Ocean melting ice such as on Mt Kenya and Mt Kilimanjaro low groundwater levels and other adverse climatic effects have been witnessed